2021
DOI: 10.1021/acsomega.1c00700
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the C-Terminal Truncated DEAD-Box Protein DDX3X With RNA and Nucleotide Substrates

Abstract: DDX3X is a human DEAD-box RNA helicase implicated in many important cellular processes. In addition to the RecA-like catalytic core, DDX3X contains N- and C-terminal domains. The ancillary domains of DEAD-box RNA helicases have been shown to modulate their interactions with RNA and nucleotide substrates. Here, with the goal of understanding the role of N- and C-terminal domains of DDX3X on the DDX3X catalytic activity, we examined the interactions of RNA substrates and nucleotides with a DDX3X construct posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Single-molecule fluorescence experiments revealed that the Laf-1 DEAD-box protein from Caenorhabditis elegans ( C. elegans ) does not bind to blunt-ended dsRNA 56 . In addition, the human ortholog of Laf-1 - the DDX3X protein - which lacked 80 residues from its C-terminal domain was unable to bind to blunt-ended dsRNA molecules; thus, these helixes did not support the C-terminal truncated DDX1 protein’s ATP hydrolysis activity 37 . Moreover, the ATPase activity of a few DEAD-box proteins is stimulated by DNA molecules 26, 27 28 29 30 31 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Single-molecule fluorescence experiments revealed that the Laf-1 DEAD-box protein from Caenorhabditis elegans ( C. elegans ) does not bind to blunt-ended dsRNA 56 . In addition, the human ortholog of Laf-1 - the DDX3X protein - which lacked 80 residues from its C-terminal domain was unable to bind to blunt-ended dsRNA molecules; thus, these helixes did not support the C-terminal truncated DDX1 protein’s ATP hydrolysis activity 37 . Moreover, the ATPase activity of a few DEAD-box proteins is stimulated by DNA molecules 26, 27 28 29 30 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The TLC assay was employed to determine the RNA length required to support the DDX1 protein ATP hydrolysis activity. TLC has been used extensively to examine the stimulation of the DEAD-box proteins’ ATP hydrolysis activity by various nucleic acid substrates 37, 38, 41 . For the experiments outlined here, we employed single-stranded RNA (ssRNA) molecules of similar sequences and different lengths.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations